Nursing students and clinical instructors’ perceptions of clinical learning environments, supervision, and teaching (CLES-T) - Ahmad, Norfadzilah; Khairul Anwar, Nurul Hamidah (IIUM Press, 2018)
Objectives: This study aimed to investigate the perceptions of International Islamic University Malaysia (IIUM) Kuantan nursing students, clinical nurse instructors, and staff nurses of the support offered to student nurses during learning in a clinical setting. Methodology: A cross-sectional study was carried out on undergraduate nursing students (n=118), and clinical instructors (n=8) at the faculty or Kulliyyah of Nursing, IIUM, using the Clinical Learning Environment, Supervision and Nurse Teacher (CLES-T) survey. Descriptive analysis was used to investigate the sociodemographic data, and further statistical tests were conducted with regard to their levels of perception. Results: Overall, the participants perceived the clinical learning environment to be good. There was no difference in perception between nursing students and the clinical nurse instructors (p>0.05). There was no significant difference in terms of gender and levels of perception (p>0.05). This study did find a significant relationship between level of study and area of posting for students and perception levels (p<0.05). Conclusion: This study showed that the majority of the students had positive perceptions of the clinical learning environment, supervision, and nurse teachers. The school provided sufficient support within the clinical learning environment in term of supervision and nurse teachers. These results will help the nursing school in terms of upgrading the clinical learning environment and encouraging collaboration with hospital management to provide a good clinical learning experience for students.